A Forward-Looking Vision for Developing Social Studies Curricula in Light of Digital Health - Athamnah, Wasan Mahmoud Mohammd (Journal of Cultural Analysis and Social Change, 2025)
The study aimed to formulate a forward-looking vision for developing social studies curricula in Jordan to integrate digital health concepts. It also aimed to identify the core themes, knowledge, skills, and values that should be included in the curriculum, and to propose a methodological and pedagogical model for integrating digital health content appropriate to different educational levels. This was achieved through a systematic literature review of local and international sources on digital health, health education themes, and social studies curricula. Expert foresight was also conducted: gathering the opinions of experts from the Ministry of Education, the Ministry of Health, and academics in education and society. It also analyzed current social studies curriculum textbooks in Jordan to identify gaps and possibilities for integration. The study sample consisted of 25 experts from the aforementioned entities, (10) geographically distributed schools (cities, villages, and desert) to test the proposed curricula, and (420) male and female students to measure the impact of the tested curricular module on awareness and skills. The results indicated a strong consensus among experts on the need to integrate digital health into social studies curricula, with teacher training a priority. Students also demonstrated significant improvements in knowledge, awareness, and attitudes after implementing the pilot module. Interactive activities (rather than indoctrination) are most effective. The study recommends developing a digital health unit/center within the social studies curriculum for each level (elementary, intermediate, and secondary) in flexible formats (classroom hours, activities via the national platform). Teachers should also be trained through an intensive, ongoing national program to prepare them to use digital health resources and lead ethical dialogues around health data.